AN ECOCRITICAL READING OF SELECTED RONGMEI NAGA FOLKTALES - Panmei, Pousuaikingliu Rikhi; Lourembam, Dhanamanjuri; Moyon, Ngoruh Engnithar Aquiline (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ecocriticism as a literary theory examines the relationship between literature and environment. Though it is a fairly recent theory, ecocriticism deviates from this anthropocentric approach to reading literature in favor of a more eco-centric perspective, in contrast to its predecessors, which typically concentrate on men and things relating to men. Ecocriticism can be applied to any work of literature since there is no set or definitive way to apply it. And as such the paper titled An Ecocritical Reading of Selected Rongmei Naga Folktales will focus on the environmental aspects of Rongmei folktales and its relevance to the contemporary environmental crisis. The importance of folktale is multitudinous, to name a few it enlighten the people of their culture, their roots, identity as well as beliefs and customs that is distinct to each tribe or community. Our forefathers used folktale as a means of passing on their knowledge to subsequent generations, so in addition to being entertaining, they are also replete with ancient wisdom. Environmental consciousness is one of them. There is a wealth of ecological wisdom to be gleaned from the tales of our forefathers when examined from an ecocritical standpoint.